(35 + 47 + 42 + x) / 4 = 50
(124 + x) / 4 = 50....multiply both sides by 4, cancelling the 4 on the left side.
124 + x = 50 * 4
124 + x = 200
x = 200 - 124
x = 76 <===
Answer:
Step-by-step explanation:
Answer:
-1
Step-by-step explanation:
Answer:
3√(22) + 7
Step-by-step explanation:
The way this is worded can be interpreted two different ways so just to cover the bases, I'll do both. I'm confident they are asking for way 1 though because it wants you to simplify the expression, not evaluate. Way 2 gives you a solution rather than an exact equation.
<u>Number 1</u>
√(6) x √(33) + 7
= √(6 x 33) + 7
= √(198) + 7
= √(9 x 22) + 7
= 3√(22) + 7
<u>Number 2</u>
√(6) x √(33 + 7)
= √(6) x √(40)
= √(6) x (4√(10))
= 4√(60)
= 8√(15)
Answer:
6^4 * 6^3
Step-by-step explanation: